2022
DOI: 10.1111/jipb.13383
|View full text |Cite
|
Sign up to set email alerts
|

R‐loop: The new genome regulatory element in plants

Abstract: An R‐loop is a three‐stranded chromatin structure that consists of a displaced single strand of DNA and an RNA:DNA hybrid duplex, which was thought to be a rare by‐product of transcription. However, recent genome‐wide data have shown that R‐loops are widespread and pervasive in a variety of genomes, and a growing body of experimental evidence indicates that R‐loops have both beneficial and harmful effects on an organism. To maximize benefit and avoid harm, organisms have evolved several means by which they tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 149 publications
(239 reference statements)
0
1
0
Order By: Relevance
“…Prevention and resolution of R-loops can occur through RNA processing factors, DNA topoisomerases, RNA:DNA helicases, ribonuclease H (RNase H) enzymes, as well as chromatin remodelers [reviewed in (21)]. We had developed an efficient R-loop profiling method ssDRIP-seq (single-strand DNA ligation-based library construction from RNA:DNA hybrid immunoprecipitation, followed by sequencing), which had been applied in multiple species to characterize R-loop formation and dynamic pattern genome-widely [ (22)(23)(24)(25)(26)(27)(28)(29)(30), reviewed in (31)]. Unexpectedly, we found that a large proportion of R-loops is correlated with H3K9me2 and H3K27me1 heterochromatic marks in Arabidopsis (22); however, the biological relevance of these observations was not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Prevention and resolution of R-loops can occur through RNA processing factors, DNA topoisomerases, RNA:DNA helicases, ribonuclease H (RNase H) enzymes, as well as chromatin remodelers [reviewed in (21)]. We had developed an efficient R-loop profiling method ssDRIP-seq (single-strand DNA ligation-based library construction from RNA:DNA hybrid immunoprecipitation, followed by sequencing), which had been applied in multiple species to characterize R-loop formation and dynamic pattern genome-widely [ (22)(23)(24)(25)(26)(27)(28)(29)(30), reviewed in (31)]. Unexpectedly, we found that a large proportion of R-loops is correlated with H3K9me2 and H3K27me1 heterochromatic marks in Arabidopsis (22); however, the biological relevance of these observations was not clear.…”
Section: Introductionmentioning
confidence: 99%